House of Falconer : Master of His Fate - Book 1 - Bradford, Barbara Taylor, 1933-2024- (New York : St. Martins Press, 2018)
Victorian England is a country of sharp divides between rich and poor, but James Lionel Falconer is everything a self-made man should be: handsome, ambitious, charming, and brimming with self-confidence. Even as a boy working in his fathers market stall in Camden, he was determined to become a merchant prince. Through hard work and a single-minded determination, James rises quickly through the ranks, with a loving wife, devoted children, and a lofty position in the Malvern & Malvern Company. But when back-to-back tragedies strike the Falconer home, shattering this idyllic life, it seems as though James might never recover his former glory... until a royal summons gives him the chance to prove that he truly is a master of the game.
Keywords: Falconer, James Lionel (Fictitious character) -- Fiction; Merchants -- Fiction; Great Britain -- History -- Victoria, 1837-1901; Fiction; Historical fiction; Domestic fiction